PERANCANGAN APLIKASI POINT OF SALES (POS) BERBASIS ANDROID DENGAN QRIS PAYMENT (STUDI KASUS: WARUNG SEBLAK TONJONG) - Nurhidayat, Ananda Rizky; Nugraha, Bagja; Hendriadi, Ade Andri (Jurnal Informatika dan Teknik Elektro Terapan, 2025)
MSMEs have an important role in the national economy, but many still use manual transaction recording, making them vulnerable to calculation errors and difficulties in tracking financial reports. To overcome this problem, an Android-based Point of Sale (POS) application integrated with the Laravel website was developed to improve operational efficiency. The method used in this research is the System Development Life Cycle (SDLC) Waterfall model, which is carried out in stages from needs analysis to implementation. The analysis shows that Warung Seblak Tonjong needs a system that is able to record automatic transactions, manage products, provide sales reports, and support digital payments with QRIS Payment. Testing is done using Black Box Testing, which ensures all features function according to specifications. The test results show that this system can help speed up transaction recording, reduce errors, and increase efficiency in financial reporting. With the implementation of this system, it is expected that Warung Seblak Tonjong and other MSMEs can more easily adapt to digital technology in business management.